Numerical Solution of Fuzzy Neutral Delay Differential Equations by Fifth Order Runge-Kutta Nystrom Method - Muthukumar, T.; Jayakumar, T.; Bharathi, D. Prasantha (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, We construct the numerical solution of a particular type of different equations, called ’Fuzzy Neutral Delay Differential Equations’ by using fifth order of Runge-Kutta method. To validate the findings, relevant examples and algorithms have been discussed in a crystal clear way. The discussion has been pursued on the statement of the analyzation between the approximate and the exact solutions and the error analysis also is examined to a bring better solution.